Russian-English false cognate interferences in foreign language learners (Eurasian Journal of Philology Science and Education, 2015)
The effect of the mother tongue on the acquisition of the foreign language is decidedly significant and has been the focus of the researchers for many decades. One of the aspects of the influence of L1 is known as language transfer or interference. Therefore, this study examines the influence of L1 lexis has on FL lexis when students carry out oral and written assignments in the FL, namely English. To respond this question, 19 students of the Foreign Languages Department at Suleyman Demirel University were requested to translate 25 sentences into English. The results of this study revealed that the influence of Russian as L1 or L2 in terms of false cognates can significantly hamper conveying meaning in the foreign language and cause misunderstanding. In addition, the research showed that the best speakers of Kazakh were the graduates of multilingual schools, who scored the highest in the study as well.
Keywords: interference; false cognates; multilingual.